Selected areas of Web 2.0 technology application in partnership enterprises - Turek, Tomasz (Wybrane obszary zastosowania technologii Web 2.0 w przedsiębiorstwach partnerskich, 2011)
The paper presents basic areas within which partnership enterprises conduct business activity and which may be supported by Web 2.0 technology. A starting point for the discussion is the nature of Web. 2.0 technology, which has recently become an important business platform. Then, the nature of partnership enterprises is presented, which, due to their geographic dispersion, become a natural sphere for the application of Web 2.0 technology.Finally, the last section of the paper presents various areas where modern technology maybe utilized, in particular: internal communication among partners, internal communication within a partnership system and communication with customers. There is also presented an example of utilizing Web 2.0 technology in making an application available with the aid of SaaS-type solutions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 248-258
Keywords: Web 2.0; partnership company; cooperation